Croatia: EU-Driven Reforms as a Wind of Change in the Public Finance Legal Framework - Žunić Kovačević, Nataša; Pisačić, Viktorija (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The legal framework of public finance in Croatia has been under the significant influence of fiscal integration within the European Union (EU). A prerequisite for analysing the impact of EU law on national fiscal governance is a prior understanding of the national fiscal framework; thus, the introductory section of this chapter presents an overview of the legal sources relevant to public finance. Special emphasis is placed on the constitutional and statutory provisions related to the budgetary process, highlighting the Croatian Parliament’s authority in adopting the central budget. In the following section, the chapter offers an overview of the constitutional foundations of fiscal federalism in Croatia. As the fiscal architecture at the subnational level is based on the two-tiered system of local self-government and regional units, this section presents the most important aspects of subnational fiscal sovereignty, remarking on the influence of EU law on fiscal decentralisation in Croatia. Thereafter, the next section explores the regulation of public debt and the tools for effective fiscal policy. Finally, this chapter investigates the interplay between EU crisis management and its implications for Croatian fiscal governance. Keywords: public finance law, budget law, fiscal policy, EU law